Manufacturing method for high thermal conductivity net-sized silicon nitride ceramic substrate

JP7641046B2Active Publication Date: 2025-03-06SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023544057
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-20
Filing Date
2022-01-17
Publication Date
2025-03-06
Estimated Expiration
2042-01-17

AI Technical Summary

Benefits of technology

【0031】 有益効果:本発明の顕著な特徴は、製造された窒化珪素セラミックス基板は焼結寸法と表面品質の精密制御を実現でき、後続の加工を必要とせずに直接使用でき、製造技術が簡単で、経済的で実用の特徴を有することである。本発明のもう一つの顕著な特徴は、製造プロセス中の酸化と不純物導入を制御することにより、窒化珪素セラミックス基板の高熱伝導性能を実現することである。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007641046000001
    Figure 0007641046000001
  • Figure 0007641046000002
    Figure 0007641046000002
  • Figure 0007641046000003
    Figure 0007641046000003
Patent Text Reader

Abstract

The present invention relates to a method for producing a high thermal conductive net-size silicon nitride ceramic substrate, which includes the following steps: (1) mixing at least one type of raw powder selected from silicon nitride powder and silicon powder, a sintering aid, a dispersant, an antifoaming agent, a binder and a plasticizer in a protective atmosphere, followed by vacuum degassing to obtain a mixed slurry; (2) performing tape casting and drying in a nitrogen atmosphere to obtain a first biscuit; (3) performing a shaping pretreatment on the obtained first biscuit to obtain a second biscuit; (4) debonding the obtained second biscuit at 500-900°C in a nitrogen atmosphere with a slight positive pressure to obtain a third biscuit; and (5) leaving the obtained third biscuit in a nitrogen atmosphere and gas pressure sintering at 1800-2000°C to obtain the high thermal conductive net-size silicon nitride ceramic substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for manufacturing a highly thermally conductive net-sized silicon nitride ceramic substrate, which belongs to the field of ceramic material manufacturing. [Background technology]

[0002] In recent years, semiconductor devices have been rapidly developing along the trend of high power, high frequency, and integration. The heat generated by the operation of a semiconductor device is an important factor that causes the failure of the semiconductor device, and the thermal conductivity of an insulating substrate is an important factor that affects the heat dissipation of the entire semiconductor device. In addition, in fields such as electric vehicles and high-speed railways, semiconductor devices often face complex mechanical environments such as shaking and vibration during use, which places strict requirements on the mechanical reliability of the materials used.

[0003] High thermal conductive silicon nitride (Si3N4) ceramics have excellent mechanical and thermal properties. Due to their excellent mechanical performance and good high thermal conductivity potential, silicon nitride ceramics are expected to make up for the shortage of existing substrate materials such as alumina and aluminum nitride, and have high market prospects for applications in high-end semiconductor devices, especially high-power semiconductor devices.

[0004] At present, the commercial application requirements for the thickness of silicon nitride ceramic substrates are concentrated at about 0.2 to 0.8 mm, and molding such thin samples is very difficult. Therefore, molding of the substrate is a core technology for realizing its batch quantification and subsequent application. At present, the molding methods of ceramic substrates mainly include tape casting, dry press molding, and press molding. Among them, it is difficult to directly manufacture ceramic substrates with a thickness of 0.5 mm or less by dry press molding due to the unevenness of powder flow and the process characteristics of mechanical pressing, and there are challenges such as accurate control of thickness and uneven thickness, so subsequent machining is required. The press molding process is complicated, and it is necessary to repeat the rolling film to remove the uneven thickness due to the limitations of the process itself and the lumps caused by the aggregation of raw materials, and the manufactured substrate is prone to bubbles and surface unevenness, and mechanical processing is also required to meet the process requirements of the subsequent copper coating.

[0005] In contrast, the tape casting process has high production efficiency, low cost, can be fully automated, and is convenient for continuous batch production, and is the process technology with the most prospects and potential for development of ceramic substrate molding, but the casting film produced in this way is prone to bubbling, cracking, deformation, uneven thickness, etc., which leads to problems such as low yield, low flatness, uneven thickness, and the need for subsequent machining. On the other hand, the ceramic substrate must have characteristics such as high flatness, uniform thickness, and surface smoothness, which are necessary conditions for the subsequent copper cladding technology. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] China Patent Application Publication No. 105884376 Summary of the Invention [Problem to be solved by the invention]

[0007] To this end, the present invention provides a method for producing a highly thermally conductive net-sized silicon nitride ceramic substrate, which includes: [Means for solving the problem]

[0008] (1) At least one raw powder selected from silicon nitride powder and silicon powder, a sintering aid, a dispersant, an antifoaming agent, a binder and a plasticizer are mixed in a protective atmosphere, and then vacuum degassed to obtain a mixed slurry, the vacuum degree of the vacuum degassing is -0.1 to -10 kPa, and the time is 6 to 24 hours; (2) Tape casting in a nitrogen atmosphere and drying using a flowing and hot N2 atmosphere with increasing temperature to obtain a first biscuit; (3) subjecting the obtained first biscuit to a pre-shaping treatment for treating the first biscuit using cold isostatic pressing to obtain a second biscuit; (4) The obtained second biscuit is debonded at 500 to 900 ° C in a nitrogen atmosphere of a slight positive pressure to obtain a third biscuit, the atmospheric pressure of the nitrogen atmosphere of the slight positive pressure is 0.12 to 0.2 MPa, and the debonding time is 1 to 3 hours; (5) The resulting third biscuit is left in a nitrogen atmosphere and gas pressure sintered at 1800 to 2000°C to obtain the highly thermally conductive, net-size silicon nitride ceramic substrate, and the crucible used for the gas pressure sintering is a high-purity BN crucible or a graphite crucible having a high-purity BN spacer layer attached to its surface.

[0009] In this disclosure, the processes of slurry preparation, vacuum degassing, tape casting, biscuit drying, biscuit shaping, debonding and sintering during the tape casting manufacturing process are designed and controlled to solve difficult problems such as foaming, cracking, deformation and uneven thickness of the casting substrate, and net-size molding of high thermal conductive silicon nitride ceramic substrate is realized.

[0010] Specifically, the casting slurry is mixed thoroughly under a protective atmosphere by ball milling, and is combined with a low vacuum long-term degassing treatment to reduce or eliminate the bubbles in the slurry and reduce the aggregation of the slurry.The cylindrical scraper and its highly precise control in the tape casting process, as well as the continuous temperature increase and hot N2 atmosphere are used to carry out drying treatment measures on the biscuit of the casting film, to realize the production of high-quality, defect-free casting film and precise control of its thickness uniformity.

[0011] Measures such as N2 protective atmosphere during ball mill mixing and tape casting are taken to inhibit secondary oxidation of silicon nitride powder raw material and ensure that the prepared silicon nitride ceramic substrate has high thermal conductivity properties.

[0012] The isotropic pressure shaping pretreatment further improves the density, thickness uniformity and flatness of the prepared casting film. The micro-positive pressure debonding technology is adopted to precisely control the escape speed of gas caused by organic matter decomposition during debonding, thereby suppressing cracks, surface peeling and the occurrence of bubbles during biscuit debonding, and avoiding the occurrence of surface defects of the substrate biscuit. The high nitrogen pressure sintering during sintering controls the distortion of the substrate biscuit during the sintering process, inhibits the decomposition of silicon nitride, and further precisely adjusts the surface roughness of the silicon nitride substrate.

[0013] Through the cooperation of the above process technologies, a net-size production of high-performance silicon nitride ceramic substrate with high thermal conductivity, high flatness, high thickness uniformity, controllable surface roughness, and consistent surface quality can be achieved, which can be directly used for subsequent copper cladding technology without the need for subsequent machining.

[0014] Preferably, in step (1), the sintering aid is a rare earth oxide and an alkaline earth metal oxide, and the amount of the sintering aid is 4.0-5.0 wt% of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid. Preferably, the rare earth oxide includes Y2O3, and the alkaline earth metal oxide includes MgO.

[0015] Preferably, in step (1), the dispersant is at least one selected from polyethylene glycol (PEG) and triethyl phosphate (TEP), and the amount added is 0.2 to 1.0 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid.

[0016] Preferably, in step (1), the antifoaming agent may be oleic acid, and the amount added is 0.2 to 1.0 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid.

[0017] Preferably, in step (1), the binder may be polyvinyl butyral (PVB), and the amount of the binder is 5 to 9 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid.

[0018] Preferably, in step (1), the plasticizer is at least one selected from diethyl phthalate (DEP), dibutyl phthalate (DBP) and polyethylene glycol (PEG), and the amount of the plasticizer added is 2 to 6 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid.

[0019] Preferably, in step (1), the protective atmosphere is a nitrogen atmosphere or an inert atmosphere, and the pressure of the protective atmosphere is 0.1 MPa.

[0020] Preferably, in step (1), the mixing method is ball mill mixing, the rotation speed of the ball mill mixing is 30 to 100 rpm, the total time is 6 to 24 hours, the vacuum degree of the vacuum degassing is -0.1 to -10 kPa, and the time is 6 to 24 hours.

[0021] Also, preferably, in step (1), at least one of silicon nitride powder and silicon powder, a sintering aid, a dispersant and an antifoaming agent are mixed in a ball mill for 3 to 12 hours, and then an adhesive and a plasticizer are added and the ball mill mixing is continued for 3 to 12 hours to obtain the mixed slurry.

[0022] Preferably, in step (2), the pressure of the nitrogen atmosphere during tape casting is 0.1 to 0.2 MPa. Preferably, in step (2), the pressure of the nitrogen atmosphere during tape casting is 0.1 to 0.2 MPa.

[0023] Preferably, when drying is performed in step (2), the nitrogen gas atmosphere is flowing nitrogen gas, the pressure is 0.1 to 0.2 MPa, the temperature is 40 to 85° C., and the total drying time is 15 to 60 minutes.

[0024] Preferably, drying is performed in at least a two-stage method, with the nitrogen temperature in the later stage being greater than the nitrogen temperature in the earlier stage, and more preferably, drying is performed in three stages including a first stage having a temperature of 40-60°C and a drying time of 5-20 minutes, a second stage having a temperature of 55-70°C and a drying time of 5-20 minutes, and a third stage having a temperature of 65-85°C and a drying time of 5-20 minutes, and the temperature of the first stage < the temperature of the second stage < the temperature of the third stage.

[0025] Preferably, in step (3), the pre-shaping treatment involves treating the first biscuit using cold isostatic pressing, the pressure of the cold isostatic pressing being 40 to 200 MPa and the time being 2 to 10 minutes.

[0026] Preferably, in step (4), the atmospheric pressure of the slightly positive nitrogen atmosphere is 0.1 to 0.2 MPa, and the debonding time is 1 to 3 hours.

[0027] Preferably, when the original powder contains silicon powder, the mass of the silicon powder is 75% or more of the mass of the original powder, which is the sum of the mass of the silicon nitride powder and the mass of the silicon nitride generated after the silicon powder is completely nitrided, and preferably, before gas pressure sintering, the third biscuit is nitrided, and the parameters of the nitriding are: the nitrogen atmosphere is a hydrogen / nitrogen mixed atmosphere with a hydrogen content of 5 vol% or less, the gas pressure is 0.1-0.2 MPa, the nitriding temperature is 1350-1450°C, and the nitriding time is 3-6 hours.

[0028] Preferably, in step (5), the pressure of the nitrogen gas atmosphere in the gas pressure sintering is 0.5 to 10 MPa, and the temperature retention time in the gas pressure sintering is 4 to 12 hours. Also, preferably, the crucible used in the gas pressure sintering is a high-purity BN crucible or a graphite crucible having a high-purity BN spacer layer attached to its surface. Among them, the purity of the high-purity BN crucible is >99%. The purity of the high-purity BN spacer layer is >99%.

[0029] In still another aspect, the present invention provides a highly thermally conductive, net-sized silicon nitride ceramic substrate manufactured according to the above-described manufacturing method, the highly thermally conductive, net-sized silicon nitride ceramic substrate having a thickness of 0.2-1.0 mm, a thickness uniformity of ±0.04 mm, a flatness of 0-0.002 mm / mm, a surface roughness of 0.3-0.8 μm, and a thermal conductivity of 80 W m -1 ·K -1 When the flatness, thickness uniformity and surface roughness of the substrate are within 0.002mm / mm, ±0.04mm and 0.3~0.8μm respectively, no machining is required and it can be directly used for the subsequent copper plating technology.

[0030] Preferably, the silicon nitride ceramic substrate has dimensions of at least 90 mm×90 mm, preferably (114-140) mm×(114-190) mm. Effect of the Invention

[0031] Beneficial Effects: The salient feature of the present invention is that the silicon nitride ceramic substrate produced can realize precise control of sintering dimensions and surface quality, can be used directly without the need for subsequent processing, and has the characteristics of simple manufacturing technology, economical and practical. Another salient feature of the present invention is that the high thermal conductivity performance of the silicon nitride ceramic substrate is realized by controlling the oxidation and introduction of impurities during the manufacturing process. [Brief description of the drawings]

[0032] [Figure 1] FIG. 1 is a diagram showing a silicon nitride ceramic substrate produced in Example 1. [Diagram 2] 1 shows the microstructure of the silicon nitride ceramic substrate produced in Example 1. [Diagram 3] 1 is a silicon nitride ceramic substrate produced in Comparative Example 3. [Figure 4] 1 is a silicon nitride ceramic substrate produced in Comparative Example 5. [Diagram 5] Table 1 shows the process parameters of the silicon nitride ceramic substrate manufactured according to the present invention. [Figure 6] Table 2 shows the performance parameters of the silicon nitride ceramic substrate produced according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0033] Hereinafter, the present invention will be further described by the following embodiments. However, it should be understood that the following embodiments are only for the purpose of illustrating the present invention and are not intended to limit the present invention.

[0034] In this disclosure, through the design and control of slurry production, vacuum degassing, tape casting, biscuit drying, biscuit molding, debonding and sintering processes during the tape casting manufacturing process, the difficult problems of silicon nitride ceramic substrates such as foaming, cracking, deformation and uneven thickness are solved, and the substrate has uniform thickness, no surface porosity and color unevenness, no need for subsequent machining, and can be directly used to manufacture silicon nitride ceramic substrates for the subsequent copper cladding process. The following is an exemplary description of the manufacturing method for high thermal conductivity net size silicon nitride ceramic substrates.

[0035] Preparation of agglomeration-free, bubble-free slurry. At least one of silicon nitride powder and silicon powder, sintering aid, dispersant, defoamer, binder and plasticizer are mixed in a ball mill under a protective atmosphere (e.g., N2 atmosphere, pressure can be 0.1 MPa), and then vacuum degassed to produce a mixed slurry without agglomeration and bubbles.

[0036] In the ball mill, silicon nitride ceramics are used for ball milling. Here, the sintering aid may be a rare earth oxide and an alkaline earth metal oxide. The rare earth oxide contains at least Y2O3, and the alkaline earth metal oxide contains at least MgO. The molar ratio of the rare earth oxide to the alkaline earth metal oxide may be (1.0-1.4):(2.5-2.9).

[0037] When the silicon powder is contained, the content of the silicon powder may be 75 to 100 wt %. The prepared slurry is subjected to a defoaming and degassing treatment by evacuation, and the degree of vacuum may be -0.1 to -10 kPa and the degassing time may be 6 to 24 hours.

[0038] Casting film biscuits with uniform thickness and no air bubbles on the surface were prepared. Tape casting was performed under N2 atmosphere (0.1-0.2 MPa). Drying was performed in a fluid and hot N2 atmosphere (flow rate 10-1000 liters / min), which realized the production of casting film biscuits with uniform thickness and no air bubbles on the surface.

[0039] As an example, tape casting was performed using a cylindrical scraper under N2 atmosphere, and the scraper height was controlled to adjust the thickness of the cast film biscuit. The cast film biscuit was dried using a fluid and hot N2 atmosphere with increasing temperature, and the temperature range of the hot N2 atmosphere was 40-85°C, and the atmospheric pressure could be 0.1-0.2MPa.

[0040] For example, there are two temperature stages, the temperature of the first stage is 40-65°C, the drying time is 15-30 minutes, the temperature range of the second stage is 60-85°C, the drying time is 15-30 minutes, and the temperature of the first stage is < the temperature of the second stage. For example, there are three temperature stages, the temperature of the first stage is 40-60°C, the drying time is 5-20 minutes, the temperature range of the second stage is 55-70°C, the drying time is 5-20 minutes, the temperature range of the third stage is 65-85°C, the drying time is 5-20 minutes, and the temperature of the first stage is < the temperature of the second stage < the temperature of the third stage.

[0041] This is the shaping pretreatment of the casting film biscuit. Under a constant pressure (40-200MPa) condition, the biscuit (substrate biscuit) of the casting film after cutting is subjected to cold isostatic shaping pretreatment to ensure the uniformity and flatness of the thickness of the casting film. However, the shaping pretreatment time may be 2-10 minutes.

[0042] This is debonding of the substrate biscuit. The substrate biscuit is heat-treated under a slight positive pressure and constant temperature conditions. As an example, by generating a slight positive pressure by passing an N2 atmosphere, the atmospheric pressure can be 0.1 to 0.2 MPa, the processing temperature can be 500 to 900°C, and the processing time can be 1 to 3 hours.

[0043] The nitridation of the substrate biscuit. When the original powder contains silicon powder, the quality of the silicon powder is 75% or more of the mass of the original powder, where the mass of the original powder is the sum of the mass of the silicon nitride powder and the mass of the silicon nitride generated after the silicon powder is completely nitrided.

[0044] In addition, when the raw powder contains silicon powder, the substrate biscuit is nitrided in a hydrogen / nitrogen mixed atmosphere with a hydrogen content of 5 vol% or less under constant temperature conditions. As an example, in a hydrogen / nitrogen mixed atmosphere with a hydrogen content of 5 vol% or less, the atmospheric pressure can be 0.1 to 0.2 MPa, the nitriding temperature can be 1350 to 1450°C, and the nitriding time can be 3 to 6 hours.

[0045] The sintering of the substrate biscuit is carried out under high pressure N2 atmosphere conditions. As an example, the substrate biscuit is sintered by placing it in a BN crucible and carrying out gas pressure sintering under high pressure N2 atmosphere conditions, in which the N2 atmosphere pressure is preferably 0.5 to 10 MPa, which is advantageous for improving the mechanical / thermal / electrical properties of the material and reducing the roughness of the substrate surface within this range. The sintering temperature can be 1800 to 2000°C, and the warming time can be 4 to 12 hours.

[0046] As described above, the manufacture of the high thermal conductive net-size silicon nitride ceramic substrate of the present invention is entirely carried out in a nitrogen atmosphere. The thickness uniformity of the silicon nitride ceramic substrate obtained by a micrometer test is 0.04 mm. The flatness of the obtained silicon nitride ceramic substrate can be measured by a profile measuring device to be 0 to 0.002 mm / mm.

[0047] The surface roughness of the silicon nitride ceramic substrate obtained was 0.3 to 0.8 μm when measured using a profile measuring device. The thermal conductivity of the silicon nitride ceramic substrate obtained was 80 W·m when measured using a laser thermal conductivity meter. -1 ·K -1 Greater than.

[0048] The present invention will be described in detail below with further examples. Similarly, the following examples are only used to further explain the present invention and cannot be understood as limiting the scope of protection of the present invention, and any non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention are all within the scope of protection of the present invention. The process parameters of the following specific examples are not limited to the specific values ​​of the following examples, but are merely examples of suitable ranges that those skilled in the art can select within a suitable range through the description of this specification.

[0049] Example 1 First, the starting ceramic powder (silicon nitride 95g), sintering aid (5g, Y2O3:MgO=1.2:2.5, molar ratio), antifoaming agent (oleic acid, 0.5g), dispersant (PEG, 0.5g), grinding balls (silicon nitride balls, 200g), and organic solvent (anhydrous ethanol, 80g) were placed in a sealed nylon ball mill tank, and after evacuation, the tank was ventilated with N2 atmosphere protection and mixed with a ball mill at 100 rpm for 4 hours. The above slurry was further added with a binder (PVB, 7g) and a plasticizer (DBP, 4g), and the slurry was ball milled under N2 atmosphere protection for 8 hours, after which a uniformly dispersed and non-agglomerated slurry was obtained.

[0050] Next, the prepared slurry was vacuumed and defoamed and degassed for 12 h, and the vacuum degree was -0.5 kPa. After that, the above-mentioned bubble-removed slurry was tape-cast using a cylindrical scraper under N2 atmosphere protection, and the thickness of the cast film biscuit was accurately controlled to 0.4 ± 0.04 mm by controlling the height of the scraper. The cast film biscuit was dried using a fluid and hot N2 atmosphere with gradually increasing temperature (flow rate 100 L / min), and the N2 atmosphere pressure was 0.1 MPa, and the hot N2 atmosphere with gradually increasing temperature consisted of three stages, the front, middle, and back, such as 45 °C (8 min), 65 °C (8 min), and 80 °C (8 min), respectively.

[0051] The biscuit was cut into 143.0mm x 143.0mm square plates using an automatic slicer, and cold isostatic pressing was performed for 5 minutes at 100MPa. The shaped biscuit was debonded for 2 hours at 700℃ in a 0.15MPa N2 atmosphere. The debonded biscuit was placed in a high-purity BN crucible (purity >99%) and then placed in a gas pressure sintering furnace, where it was sintered at 1900℃ for 10 hours in a 5MPa N2 atmosphere, and then cooled to room temperature by the furnace.

[0052] The silicon nitride ceramic substrate produced in this Example 1 is shown in FIG. 1, with dimensions of 114.4 mm × 114.4 mm, dimensional deviation of ±0.1 mm, thickness of 0.32 ±0.02 mm, flatness of 0.2 mm, and surface roughness of 0.4 μm. The thermal conductivity of the material is 95 W / (m·K), and the bending strength is 780 MPa. This substrate does not require subsequent machining and can be directly used in the subsequent copper cladding process. Its cross-sectional microstructure can be seen in FIG. 2, and the microstructure is uniform and dense.

[0053] Examples 2 to 5 The raw material mixing ratio and composition, and the process refer to Example 1. Specific parameters such as slurry preparation, vacuum degassing, tape casting, biscuit molding, debonding and sintering bonding processes are shown in Table 1 in Figure 5, and the properties of the manufactured substrate material are shown in Table 2 in Figure 6.

[0054] Example 6 First, the starting ceramic powder (silicon nitride 3g, silicon powder 55g), sintering aid (4.5g, Y2O3:MgO=1.1:2.9, molar ratio), antifoaming agent (oleic acid, 0.3g), dispersant (PEG, 0.3g), polishing balls (silicon nitride balls, 120g), and organic solvent (anhydrous ethanol, 50g) were placed in a sealed nylon ball mill tank, evacuated, passed through a N2 atmosphere protection, and mixed with a ball mill at 100 rpm for 4 hours. The binder (PVB, 5g) and plasticizer (DBP, 3g) were further added to the above slurry, and the mixture was ball milled under a N2 atmosphere protection for 8 hours to obtain a uniformly dispersed and non-agglomerated slurry.

[0055] Next, the prepared slurry was vacuumed and defoamed and degassed for 12 h, and the vacuum level was -0.5 kPa. After that, the slurry after removing the bubbles was tape-cast using a cylindrical scraper under N2 atmosphere protection, and the thickness of the cast film biscuit was accurately controlled to 0.5 ± 0.05 mm by controlling the scraper height. The cast film biscuit was dried using a fluid and hot N2 atmosphere with gradually increasing temperature (flow rate 50 L / min). The N2 atmosphere pressure was 0.2 MPa, and the hot N2 atmosphere with gradually increasing temperature consisted of three stages, the front, middle, and back, at 45 °C (6 min), 65 °C (6 min), and 80 °C (6 min), respectively.

[0056] The biscuit was cut into a square plate of 142.6 mm × 194.4 mm using an automatic slicer, and cold isostatic pressing was performed for 3 minutes at 150 MPa. The shaped substrate biscuit was debonded for 2 hours at 700 ° C in a 0.15 MPa N2 atmosphere. The debonded substrate biscuit was nitrided for 6 hours at 1450 ° C in a 0.2 MPa N2 (containing 5% H2) atmosphere. The substrate biscuit after nitriding was placed in a high-purity BN crucible (purity > 99%), then placed in a gas pressure sintering furnace, and sintered at 1900 ° C for 10 hours in a 5 MPa N2 atmosphere, and then cooled to room temperature by the furnace. The properties of the prepared substrate material are shown in Table 2.

[0057] Examples 7 to 9 The raw material mixing ratio, composition, and process refer to Example 6. The specific parameters of the slurry production, vacuum degassing, tape casting, biscuit molding, debonding, nitriding treatment and sintering processes are shown in Table 1, and the properties of the produced substrate material are as shown in Table 2.

[0058] Example 10 The silicon nitride ceramic substrate in this Example 10 was manufactured in accordance with Example 1, with the difference being that the substrate was cut into square plates of 200 mm×200 mm using an automatic slicer, and cold isostatically pressed at 100 MPa.

[0059] Example 11 The manufacturing process of the silicon nitride ceramic substrate in this Example 11 was the same as that in Example 6, except that the substrate was cut into square plates of 200 mm×200 mm using an automatic slicer and cold isostatically pressed at 100 MPa.

[0060] Comparative Example 1 The specific parameters of the raw material mixing ratio and composition, slurry preparation, vacuum degassing, tape casting, debonding and sintering process are shown in Table 1. The process refers to Example 1, with the difference that no biscuit shaping pretreatment is performed. The properties of the prepared substrate material are shown in Table 2. Since the tape casting substrate biscuit is not subjected to isostatic pressure shaping pretreatment, the thickness uniformity and flatness of the prepared substrate are obviously reduced, and the thermal conductivity is also slightly reduced.

[0061] Comparative Example 2 The specific parameters of the raw material mixing ratio and composition, slurry preparation, vacuum degassing, tape casting, biscuit molding, debonding and sintering process are shown in Table 1. The process refers to Example 1, with the difference that high nitrogen gas pressure was not used for high temperature sintering, and only 0.1MPa N2 protective atmosphere was used. The properties of the prepared substrate material are shown in Table 2. The surface roughness of the prepared substrate was obviously increased because the gas pressure sintering of high nitrogen atmosphere was not used, and the substrate surface roughness requirements of the subsequent copper cladding process could not be met.

[0062] Comparative Example 3 The specific parameters of the raw material mixing ratio and composition, slurry preparation, vacuum degassing, tape casting, biscuit molding, debonding and sintering process are shown in Table 1. The process refers to Example 1, with the difference being that micro-positive pressure debonding is not adopted (vacuum condition debonding is adopted). The properties of the prepared substrate material are shown in Table 2. Because vacuum debonding is adopted, the escape speed of organic matter decomposing and generating gas during the debonding process cannot be controlled (it is too fast), and there are localized microcrack defects on the prepared substrate surface (see Figure 3).

[0063] Comparative Example 4 The specific parameters of the raw material blending ratio and composition, slurry production, tape casting, biscuit molding, debonding and sintering process are shown in Table 1. The process refers to Example 1, with the difference being that no vacuum degassing measures are adopted. The properties of the prepared substrate material are shown in Table 2. Because no vacuum degassing measures are adopted, there are a small number of bubbles in the slurry, and small bubble defects exist locally on the surface of the prepared substrate.

[0064] Comparative Example 5 The specific parameters of the raw material mixing ratio and composition, slurry preparation, vacuum degassing, tape casting, biscuit molding, debonding and sintering process are as shown in Table 1. The process refers to Example 1, the difference is that the high purity BN crucible is not used as the container for high temperature sintering of silicon nitride substrate biscuit, but is directly placed in the graphite crucible. The properties of the prepared substrate material are shown in Table 2. Because the high purity BN crucible is not used, the graphite crucible is easy to contaminate the substrate, and the surface uniformity of the produced substrate is poor, and there are local color unevenness defects (see Figure 4).

[0065] Comparative Example 6 The specific parameters of the raw material mixing ratio and composition, slurry preparation, vacuum degassing, tape casting, biscuit molding, debonding and sintering process are shown in Table 1. The process refers to Example 1, the difference is that the air atmosphere is used for the ball mill process of the slurry. Because the nitrogen gas atmosphere protection is not used, the silicon nitride powder raw material will be oxidized to a certain extent during the ball milling process, and the thermal conductivity of the produced silicon nitride ceramic substrate is low.

Claims

1. A method for manufacturing a high thermal conductivity net-sized silicon nitride ceramic substrate, comprising the steps of: (1) mixing at least one raw powder selected from silicon nitride powder and silicon powder, a sintering aid, a dispersant, an antifoaming agent, a binder and a plasticizer in a protective atmosphere, and then vacuum degassing to obtain a mixed slurry, the vacuum degree of the vacuum degassing being -0.1 to -10 kPa and the time being 6 to 24 hours; (2) Tape casting and drying the mixed slurry in a nitrogen atmosphere to obtain a first bisque body, and a fluid and hot N 2 atmosphere with an increasing temperature is used in the drying; (3) subjecting the obtained first bisque body to a pre-shaping treatment using cold isostatic pressing to treat the first bisque body, thereby obtaining a second bisque body; (4) The obtained second bisque body is peeled off at 500 to 900 ° C. in a nitrogen atmosphere of a slightly positive pressure to obtain a third bisque body, the atmospheric pressure of the nitrogen atmosphere of the slightly positive pressure is 0.12 to 0.2 MPa, and the peeling time is 1 to 3 hours; (5) The obtained third bisque body is left in a nitrogen atmosphere and gas pressure sintered at 1800 to 2000°C to obtain the high thermal conductive net-size silicon nitride ceramic substrate, and the crucible used for the gas pressure sintering is a high purity BN crucible or a graphite crucible having a high purity BN spacer layer attached to its surface; In step (1), the sintering aid is a rare earth oxide and an alkaline earth metal oxide, and the amount of the sintering aid is 4.0 to 5.0 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid; the dispersant is at least one selected from polyethylene glycol (PEG) and triethyl phosphate (TEP), and the amount of the dispersant added is 0.2 to 1.0 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid; The defoaming agent is oleic acid, and the amount of the defoaming agent added is 0.2 to 1.0 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid; The binder is polyvinyl butyral (PVB), and the amount of the binder is 5 to 9 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid; The plasticizer is at least one selected from diethyl phthalate (DEP), dibutyl phthalate (DBP) and polyethylene glycol (PEG), and the amount of the plasticizer added is 2 to 6 wt % of the total mass of the silicon nitride powder, the silicon nitride formed by completely nitriding the silicon powder, and the sintering aid. The present invention relates to a method for producing a silicon nitride ceramic substrate having high thermal conductivity and a net size.

2. The rare earth oxide is Y 2 O 3 wherein the alkaline earth metal oxide comprises MgO. The method of claim 1 .

3. In step (1), the protective atmosphere is a nitrogen atmosphere or an inert atmosphere, the pressure of the protective atmosphere is 0.1 MPa, the mixing method is ball mill mixing, the rotation speed of the ball mill mixing is 30 to 100 rpm, and the total time is 6 to 24 hours. The method of claim 1 .

4. In step (2), the pressure of the nitrogen atmosphere during tape casting is 0.1 to 0.2 MPa; When drying is performed, the nitrogen atmosphere is flowing nitrogen gas, the pressure is 0.1-0.2 MPa, the temperature is 40-85° C., and the total drying time is 15-60 minutes. The method of claim 1 .

5. In step (3), the cold isostatic pressing is performed at a pressure of 40 to 200 MPa for a time of 2 to 10 minutes. The method of claim 1 .

6. In step (5), the pressure of the nitrogen gas atmosphere in the gas pressure sintering is 0.5 to 10 MPa, and the temperature retention time in the gas pressure sintering is 4 to 12 hours. The method of claim 1 .

Citation Information

Patent Citations

  • Method for preparing silicon-nitride ceramic substrate through silicon-powder tape casting

    CN105884376A

  • Silicon nitride ceramic slurry, preparation method of silicon nitride ceramic slurry and application of silicon nitride ceramic slurry in preparing silicon nitride cast film

    CN107857595A

  • Production of sintered silicon nitride having high density

    JP1993170548A

  • Silicon nitride circuit board and module using the same

    JP2013182983A

  • Silicon nitride-based sintered body, and abrasion-resistant member including the same

    JP2016050137A